Use of cassava in livestock and aquaculture feeding programs - Lukuyu, Ben A.; Okike, Iheanacho; Duncan, Alan J.; Beveridge, Malcolm C.M.; Blümmel, Michael (International Livestock Research Institute, 2014)
This report reviews and reassesses the present state of knowledge concerning the use of cassava products in livestock and aquaculture feeds. An ultimate objective of summarizing these data is to provide a foundation for establishing reliable and practical guidelines by which more efficient utilization of cassava products and byproducts may enhance livestock and aquaculture feeding programs, particularly in West Africa.